Check and mate to exosomal extracellular miRNA: new lesson from a new approach - Turchinovich, Andrey; Tonevitsky, Alexander G.; Cho, William C.; Burwinkel, Barbara (Frontiers in Molecular Biosciences, 2015)
MicroRNAs (miRNAs) are 19–24 nt single-stranded RNAs which regulate gene expression by sequence-specific targeting of corresponding mRNAs. Extracellular miRNAs have been consistently detected in all human body fluids, and were shown to be prominent noninvasive biomarkers for various diseases including cancer. Albeit biological function of cell-free miRNA remains questionable, multiple reports demonstrated that exosomes encapsulated extracellular miRNAs could mediate inter-cellular signaling. While others suggested that these miRNAs are mostly by-products of cell activity and do not carry any significant biological function. This perspective article is aimed to review current theories of origin of extracellular miRNA, and to highlight a recent application of a novel technique of micro-vesicles counting, that may challenge the existence of exosomal miRNA.